Normal ATXN3 Allele but Not CHIP Polymorphisms Modulates Age at Onset in Machado–Joseph Disease - França Jr, Marcondes C.; Emmel, Vanessa E.; D'Abreu, Anelyssa; Maurer-Morelli, Claudia V.; Secolin, Rodrigo; Bonadia, Luciana C.; Silva, Marilza S.; Nucci, Anamarli; Jardim, Laura B.; Saraiva-Pereira, Maria Luiza; Marques Jr, Wilson; Paulson, Henry; et al. (Frontiers in Neurology, 2012)
Background: Age at onset (AO) in Machado-Joseph disease (MJD) is closely associated with the length of the CAG repeat at the mutant ATXN3 allele, but there are other intervening factors. Experimental evidence indicates that the normal ATXN3 allele and the C-terminal heat shock protein 70 (Hsp70)-interacting protein (CHIP) may be genetic modifiers of AO in MJD. Methods: To investigate this hypothesis, we determined the length of normal and expanded CAG repeats at the ATXN3 gene in 210 unrelated patients with MJD. In addition, we genotyped five single nucleotide polymorphisms (SNPs) within the CHIP gene. We first compared the frequencies of the different genotypes in two subgroups of patients who were highly discordant for AO after correction for the length of the expanded CAG allele. The possible modifier effect of each gene was then evaluated in a stepwise multiple linear regression model. Results: AO was associated with the length of the expanded CAG allele (r2 = 0.596, p<0.001). Frequencies of the normal CAG repeats at the ATXN3 gene and of CHIP polymorphisms did not differ significantly between groups with highly discordant ages at onset. However, addition of the normal allele improved the model fit for prediction of AO (r2 = 0.604, p=0.014). Indeed, we found that the normal CAG allele at ATXN3 had a positive independent effect on AO. Conclusion: The normal CAG repeat at the ATXN3 gene has a small but significant influence on AO of MJD.